Menakar Nalar Sahabat Nabi SAW: Sebuah Tinjauan Sosio-Antropologis - Muhammad Zain (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2007)
The companions were the ones who witnessed the revelation, but they did not share a uniform perspective in understanding the text of the revelation. This phenomenon indicates that the complex situations and conditions during their time led to differences in the interpretation of the text. Therefore, the diversity of religious paradigms is inevitable. The main issue is that Islam, as understood by the companions, was an open Islam, not a rigid one. Islam was open to accommodating local ethnic values that were undoubtedly in line with Islamic law. This article attempts to elaborate on the various religious paradigms of the companions through a socio-anthropological approach.